Characterizing positive and negative 'voicers' in elite sport teams: The role of the Five Factor Model and narcissism in players' frequency and passing on of voice. (May 2020) - Van Puyenbroeck, Stef; Stouten, Jeroen; Hofmans, Joeri; Van Meervelt, Koen; Vande Broek, Gert
Abstract: Objective: This study examined the role of the Five Factor Model and grandiose narcissism in players' positive (i.e., constructive voice, supportive voice) and negative voice (i.e., defensive voice, destructive voice) in elite sport teams. Method: Players from six field hockey and seven korfball teams from the two highest national levels were assessed for four weeks. Using social network analyses, players' personality was related to their self-reported voice frequency, their voice frequency as perceived by all teammates (other-ratings), and the extent to which they pass on voice. Results: Extraversion was positively related to players' frequency of positive and negative voice. Other traits such as conscientiousness and emotional stability were only related to, respectively, positive or negative types of voice. Not all personalities (e.g., extraversion) were consistent in how they assess their own voice versus how others perceive this. Interestingly, traits such as extraversion, emotional stability and the agentic facet of narcissism were found to predict the passing on of voice. Conclusion: This study explored the importance of personality for (a) players' frequency of a differentiated set of positive and negative voice and (b) the extent to which they function as 'gates' that more covertly pass on voice. Further, the results provide perspective on how specific personalities view their voice behavior versus how their teammates perceive their voice behavior. In this way, this study is a first step in identifying players who have the potential to endanger or strengthen a team in a clear or subtle, yet influential way. Highlights: The Five Factor Model predicts positive and negative voice in elite sport teams. Particular personalities are not aware of how their voice is perceived by teammates. Narcissists and neurotics covertly pass on negative types of voice.